Side-to-side differences in overuse running injury susceptibility: A retrospective study - Zifchock, R. A.; Davis, I.; Higginson, J.; McCaw, S.; Royer, T. (Human Movement Science, 2008)
Despite the number of studies examining factors associated with overuse running injury, little is known about why an individual gets injured on a particular side of the body. Abnormal levels of several strength, structural, kinetic, and kinematic factors have been attributed to injury susceptibility. However, while most studies have compared the injured limb of injured runners to an arbitrary limb of healthy controls, there is some evidence to suggest that injury risk is related to characteristics on both sides of a runner. Therefore, the purpose of this study was to investigate how bilateral characteristics of strength, structural, kinetic, and kinematic factors relate to overuse injury. The first purpose was to compare these factors between the injured and uninjured limbs of runners with a history of injury on only one side of their bodies. The results showed that hip internal rotation range of motion and peak tibial acceleration were both elevated on the side with a history of injury. The second purpose was to compare asymmetry levels between the injured runners and runners who had never sustained a running-related injury. Asymmetry levels were similar between groups for all variables, which suggests that some level of asymmetry is normal. The final purpose of the study was to compare bilateral values of these factors between the injured and uninjured runners. The results showed that hip internal rotation range of motion, as well as the deviation from normal arch height index, were bilaterally elevated in the injured runners. Although peak tibial acceleration was different between sides of the injured runners, it was not bilaterally elevated compared to the uninjured runners. These results support the notion that injury risk may be related to risk factors on both sides.